Records of sea-ice extent and air temperature at the Sea of Okhotsk from an ice core of Mount Ichinsky, Kamchatka - Matoba S.; Shiraiwa T.; Tsushima A.; Sasaki H.; Muravyev Y.D. (My University, 2011)
The Sea of Okhotsk is the southernmost area in the Northern Hemisphere where seasonal sea ice is produced every year. The formation of sea ice drives thermohaline circulation in the Sea of Okhotsk, and this circulation supports the high productivity in the region. However, recent reports have indicated that sea-ice production in the Sea of Okhotsk is decreasing, raising concern that the decreased sea ice will affect not only circulation but also biological productivity in the sea. To reconstruct climatic changes in the Sea of Okhotsk region, we analyzed an ice core obtained from Ichinskaya Sopka (Mount Ichinsky), Kamchatka. We assumed that the remarkable negative peaks of δD in the ice core were caused by expansion of sea ice in the Sea of Okhotsk. Melt feature percentage (MFP), which indicates summer snowmelt, showed high values in the 1950–60s and the mid-1990s–2000s. The high MFP in the 1950–60s was assumed to be caused by an increase in cyclone activity reaching Kamchatka during a negative period of the Pacific Decadal Oscillation index, and that in the 1990–2000s may reflect the increase in solar irradiation during a positive period of the summer Arctic Oscillation index.
Keywords: 37.23.29 Климаты прошлого. Изменение климата; 37.29.35 Современное оледенение; 38.37.25 Вулканология; Ичинский